Empathy-driven care in the intensive care unit: exploring nurses’ experiences and perceptions - Rai, Neha (International Journal Of Community Medicine And Public Health, 2025)
Empathy is a cornerstone of high-quality nursing care, especially in high-stakes environments like the intensive care unit (ICU), where patients often face life-threatening conditions. Despite its recognized importance, the experience and perception of empathy among ICU nurses remain under-explored, particularly in diverse clinical settings such as India. This narrative review aims to explore global and Indian research on nurses’ experiences and perceptions of empathy in ICU care, identify key influencing factors, and highlight implications for practice and policy. Following the preferred reporting items for systematic reviews and meta-analyses (PRISMA) framework, an extensive literature search was conducted across PubMed, Scopus, CINAHL, Science Direct, and Google Scholar for articles published between January 2015 and April 2024. Of the 212 records initially retrieved, 20 studies were included after full-text screening based on relevance, population, and methodological quality. Findings suggest that while ICU nurses globally acknowledge empathy as vital to patient care, they often face barriers such as emotional burnout, high workload, lack of training, and institutional stress. Indian studies echoed similar themes, highlighting additional challenges such as staffing shortages and limited psychological support. Facilitators of empathy included peer support, leadership engagement, and structured communication training. Empathy in ICU nursing is both essential and complex, influenced by systemic, emotional, and cultural factors. Addressing these challenges through education, organizational support, and policy interventions may enhance empathetic care and improve patient outcomes. Future research should focus on context-specific interventions, especially in low- and middle-income countries like India.